Building Envelope Thermal Upgrade for School Buildings in Jordan. (June 2019) - Ali, H H; Al-Hashlamun, R
Abstract: Following the educational reform in Jordan in 2003, the government decided to cease the construction of old, prototypical, and uninsulated schools in favor of thermally insulated site-specific buildings. However, more than 2917 uninsulated school buildings built before the reform have continued to function. Therefore, this research focuses on evaluating and comparing the thermal efficiency of the envelope of old, uninsulated prototypical schools with that of thermally insulated, site-specific school's buildings in Jordan. Furthermore, it will develop envelope retrofit strategies for the remaining 2917 uninsulated schools. The proposed envelope retrofit alternatives will be analyzed in terms of potential energy saving and initial cost, based on which a holistic approach is developed by combining energy-efficient and economically feasible retrofitting alternatives. The research here uses mixed design methods to fulfill its purposes, including data collection from the literature and national archives, self-reported data, field monitoring of environmental parameters inside classrooms, and energy simulation using (Design Builder) software, in addition to economic analysis using the simple payback period analyses method. Based on analyses, a holistic approach to envelope retrofitting was developed for old governmental school models in Jordan, based on an analysis of the effects of the enhancement of envelope parameters on annual cooling and heating energy saving (walls, roof insulation, roof reflectance, windows, and shading elements). The proposed alternatives to envelope retrofitting for each envelope parameter was analyzed in terms of potential energy saving and initial cost analysis.